The azetidine derivative, KHG26792 protects against ATP-induced activation of NFAT and MAPK pathways through P2X7 receptor in microglia - Kim, Eun-A; Cho, Chang Hun; Kim, Jiae; Hahn, Hoh-Gyu; Choi, Soo Young; Yang, Seung-Ju; Cho, Sung-Woo (ELSEVIER, 2015)
Azetidine derivatives are of interest for drug development because they may be useful therapeutic agents. However, their mechanisms of action remain to be completely elucidated. Here, we have investigated the effects of 3-(naphthalen-2-yl(propoxy)methyl)azetidine hydrochloride (KHG26792) on ATP-induced activation of NFAT and MAPK through P2X7 receptor in the BV-2 mouse microglial cell line. KHG26792 decreased ATP-induced TNF-alpha release from BV-2 microglia by suppressing, at least partly, P2X7 receptor stimulation. KHG26792 also inhibited the ATP-induced increase in IL-6, PGE2, NO, ROS, CXCL2, and CCL3. ATP induced NFAT activation through P2X7 receptor, with KHG26792 reducing the ATP-induced NFAT activation. KHG26792 inhibited an ATP-induced increase in iNOS protein and ERK phosphorylation. KHG26792 prevented an ATP-induced increase in MMP-9 activity through the P2X7 receptor as a result of degradation of TIMP-1 by cathepsin B. Our data provide mechanistic insights into the role of KHG26792 in the inhibition of TNF-alpha produced via P2X7 receptor-mediated activation of NFAT and MAPK pathways in ATP-treated BV-2 cells. This study highlights the potential use of KHG26792 as a therapeutic agent for the many diseases of the CNS related to activated microglia. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: TUMOR-NECROSIS-FACTOR; FACTOR-ALPHA RELEASE; 2-CYCLOPROPYLIMINO-3-METHYL-1,3-THIAZOLINE HYDROCHLORIDE; TRANSCRIPTION FACTORS; NUCLEAR-FACTOR; TNF-ALPHA; CELLS; INFLAMMATION; KINASE; MODEL